2016
DOI: 10.3390/met6100251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mg17Al12 Fraction on Mechanical Properties of Mg-9%Al-1%Zn Cast Alloy

Abstract: In the current study it was observed that the offset yield point of Mg-9%Al-1%Zn alloy was strongly influenced by the connectivity of Mg 17 Al 12 . It was suggested that an increase in the fraction of Mg 17 Al 12 from 8% to 11% could lead to the formation of a Mg 17 Al 12 network which resulted in a higher offset yield point. In addition, it was observed that elongation to failure of the Mg-9%Al-1%Zn alloy strongly depended on the fraction of Mg 17 Al 12 . Moreover, the apparent toughness showed a strong inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…As shown in Figure 8a, three phases are surrounded by primary Mg matrix. According to the element mapping (see Figure 8b-f) and previous literatures [19,23,28,32], it can be deduced that the coarse irregular phase, white polygon particles, and small concentrated particles are Mg 17 Al 12 , Al 8 Mn 5 , and VB 2 intermetallic compound, respectively. Although it can be observed that some VB 2 particles are surrounded by Mg 17 Al 12 phase, the isolated VB 2 particles embedded in primary Mg matrix still can be found.…”
Section: Discussionmentioning
confidence: 62%
“…As shown in Figure 8a, three phases are surrounded by primary Mg matrix. According to the element mapping (see Figure 8b-f) and previous literatures [19,23,28,32], it can be deduced that the coarse irregular phase, white polygon particles, and small concentrated particles are Mg 17 Al 12 , Al 8 Mn 5 , and VB 2 intermetallic compound, respectively. Although it can be observed that some VB 2 particles are surrounded by Mg 17 Al 12 phase, the isolated VB 2 particles embedded in primary Mg matrix still can be found.…”
Section: Discussionmentioning
confidence: 62%
“…Lower and upper values of the ingate height were determined by means of simulation program NovaFlow&Solid through the module NovaShot, which determined maximal and minimal gating channel height for particular die-cast parts. Other values were determined to provide diverse loading modes of the mold shaping cavity [19,20].…”
Section: Characteristic Of Monitored Parametersmentioning
confidence: 99%
“…The volume fraction of the β-Mg17Al12 phase decreased with time and temperature. These secondphase particles have been found to affect the mechanical properties of magnesium alloys [16,[18][19][20]. Although the results show significant differences in tensile properties, ductility is still a concern, which seem to be insufficient for high performance industrial applications.…”
Section: Introductionmentioning
confidence: 99%